PENGARUH KESADARAN MEREK, HARGA DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE XIAOMI DI KOTA TERNATE - Ibnu Sina Hi. Yusuf; Sulfi Abdulhaji; Muhammad Rizky Pribadi Sarfan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2019)
This study aims to determine: (1) The Effect of Brand Awareness on the Purchase Decision of Xiaomi Brand Samartphone, (2) Price Effect on Xiaomi Brand Samartphone Purchase Decisions, (3) Word of Mouth Effect on Xiaomi Brand Samartphone Purchase Decisions. Quantitative research type. the population in this study are all Consumers who use Xiaomi Brand Smartphones located in Ternate City. The sampling technique uses purposive sampling method, because it uses characteristics and criteria. The characteristics and criteria in question are respondents who have made or made decisions directly to buy Xiaomi Smartphones and respondents who have Xiaomi Smartphones that have used it for at least 1 year. The number of samples is 90 respondents. The analysis technique used in this study is multiple linear regression analysis which is operated through the SPSS program. The results of this study indicate that the Brand Awareness variable has a significant effect on the purchase decisions of Xiami brand smartphones, Price has a significant effect on purchasing decisions of Xiaomi brand smartphones, Word of Mouth has a significant effect on Xiaomi brand smartphone purchase decisions. This is indicated by the value of R Square is 0.664 (66.4%) which means that the proportion of diversity in explaining the purchase decision variable (Y) is explained by the three independent variables in the regression model of 66.4% while the other variables not examined in this test are 33.6%.